Orthostatic hypotension and REM sleep behaviour disorder: impact on clinical outcomes in α-synucleinopathies. Issue 11 (29th May 2019) - Pilotto, Andrea; Romagnolo, Alberto; Tuazon, Jasmine A; Vizcarra, Joaquin A; Marsili, Luca; Zibetti, Maurizio; Rosso, Michela; Rodriguez-Porcel, Federico; Borroni, Barbara; Rizzetti, Maria Cristina; Rossi, Carlo; Vizcarra-Escobar, Darwin; et al.
Abstract : Objective: Review the effect of orthostatic hypotension (OH) and rapid-eye-movement sleep behavioural disorder (RBD) on survival, cognitive impairment and postural stability, and discuss pathogenic mechanisms involved in the association of these two common non-motor features with relevant clinical outcomes in α-synucleinopathies. Methods: We searched PubMed (January 2007–February 2019) for human studies of OH and RBD evaluating cognitive impairment, postural instability, and survival in Parkinson's disease (PD), dementia with Lewy bodies (DLB), multiple system atrophy (MSA) and pure autonomic failure (PAF). Included studies were analysed for design, key results and limitations as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: OH and RBD showed a positive association with cognitive impairment in PD and DLB, conflicting association in PAF, and no association in MSA. OH was correlated with incident falls and postural instability in PD and DLB but not in MSA. The association between RBD and postural instability was inconclusive; positive in five studies, negative in seven. OH, but not RBD, correlated with reduced survival in PD, DLB and MSA. The combination of OH and RBD was associated with cognitive impairment and more rapid progression of postural instability. Conclusions: OH and RBD yielded individual and combined negative effects on disability in α-synucleinopathies, reflecting a 'malignant' phenotype of PD with early cognitive impairment and postural instability. Underlying mechanisms may include involvement of selected brainstem cholinergic and noradrenergic nuclei.